NEW PARADIGM OF TOURISM INDUSTRY MODERNIZATION IN THE DIGITAL ECONOMY CONDITIONS (Journal of Economic Research & Business Administration, 2019)
The article discusses the modern features of the tourism industry, its role and importance in the country's economy, the quantitative and qualitative changes that take place in this area, including the number of employees, average wages, investments, the degree of depreciation of fixed assets of tourist organizations. The article analyzes the current information state of development of the tourism industry, considers the meaningful change in business processes in tourism when introducing new information and communication technologies, shows that in the digital economy, information becomes the key and determining factor in the development of tourism activities. It is shown that in tourism the main element in the formation of tourist services is information that is consonant with the modern paradigm of the digital economy. The statistics of the development of the information and communication technology sector, which provides opportunities for the functioning of the digital economy, is presented. The characteristic of the information space of the tourism industry, the latest digital technologies that are beginning to be used in the tourism industry is given.